Existence and asymptotic behavior of the positive solutions of neutral impulsive differential equations - Dimitrova, M.B.; Donev, V.I. (Нелінійні коливання, 2005)
In this article we consider first order neutral impulsive differential equations with constant coefficients and constant delays. We study the asymptotic behavior of the eventually positive solutions of these equations and establish necessary and sufficient conditions for the existence of such solutions.